Sistem Pemesanan Lapangan Futsal Maestro Berbasis Web di Kemayoran - Christian Andrew; Arie Kusumawati (UNIVERSITAS KALBIS, 2022)
Maestro Futsal since in 2014, where businees entities in the field of futsal rental services, the field booking system at maestro futsal currently still uses conventional method to order field, This study aims to build a web-based online ordering information system using prototyping system development methods, system Unified Modeling Language (UML), system programming using the Hypertext Preprocessor (PHP), and the system using Black Box Testing. The results of this study area stem that can be used to make online field reservations at Maestro Futsal and see the price of the order